2013
DOI: 10.3109/09638288.2013.814723
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and low back pain: the role of subgroups based on the avoidance-endurance model

Abstract: The results indicate different pathways to chronic pain and disability with physical underuse in FAR patients and overuse/overload in endurance patients suggesting the need for individually targeted cognitive-behavioral treatments in the maladaptive groups. Implications for Rehabilitation Improving the return to a normal physical activity level is an important goal for the rehabilitation of patients after lumbar disc surgery. Different pathways to chronic pain and disability with physical underuse in fear-avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 57 publications
5
27
2
1
Order By: Relevance
“…While one study has linked lower levels of objective physical activity to self-reported activity avoidance, 16 other studies investigating differences in objective physical activity levels based on an individual's self-reported activity pattern have found no significant differences in chronic pain samples. 17,18 This is not surprising as everyone has a different physical capacity and in a chronic pain population this would not be exclusively determined by avoiding or persisting with activity.…”
Section: 11mentioning
confidence: 97%
“…While one study has linked lower levels of objective physical activity to self-reported activity avoidance, 16 other studies investigating differences in objective physical activity levels based on an individual's self-reported activity pattern have found no significant differences in chronic pain samples. 17,18 This is not surprising as everyone has a different physical capacity and in a chronic pain population this would not be exclusively determined by avoiding or persisting with activity.…”
Section: 11mentioning
confidence: 97%
“…Persistence behaviour patterns have been identified in a substantial subgroup of chronic pain patients 19 , and empirical support for the avoidance and endurance model is starting to accumulate 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…31,34 The adaptive group has shown moderate levels of self-reported avoidance and endurance and the lowest levels of pain intensity and disability besides moderate physical activity. 34 In sum, inflexible recommendation of high levels of exercise and activity do not appear to benefit patients. Until now, there have been difficulties in the definition of a level of overactivity and/or underactivity in general and to recommend strategies of pacing activities in daily life.…”
Section: Optimizing the Method: Individually Targeting Patient Reassumentioning
confidence: 99%